TINJAUAN CUSTOMER SERVICE DIGITAL DI ERA 4.0PADA BANK CENTRAL ASIA - Nindya Rahma Anindisha (2023)
International bank in Indonesia, Bank Central Asia (BCA) is the best bank in terms of asset quality and customer service. In the world of banking, customer service is important in carrying out marketing strategies. Therefore, BCA requires special skills for employees to create an atmosphere that is different from the previous atmosphere and always innovates to keep up with the times where the 4.0 era continues. In this study, the authors used Field Research, namely in-depth research which resulted in a complete and well-organized description of the unit. Researching by asking directly to customer service, other employees of Bank Central Asia (BCA). The approach used is a qualitative approach. Amid the emergence of many digital banks, BCA is making efforts to improve manual customer service by conducting training or training that is closer to customers, especially generation Z customers. This can also be done by improving the quality of human resources, and strengthening solution centers. Digital Customer Service has artificial intelligence capabilities like humans, but there is one thing that humans cannot replace, namely the heart. Because with a human heart one can have extraordinary empathy and patience to build progress in the level of education in Indonesia.